2016
DOI: 10.1111/adj.12316
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of forensic odontology among dentists in Australia: are they keeping forensically valuable dental records?

Abstract: Background Forensic odontologists provide an important service to the community by identifying unknown deceased people, allowing both legal outcomes and family closure. Non‐visual identification may be achieved by comparison of post‐mortem data with ante‐mortem dental records provided by oral health practitioners. Success is dependent largely on the accuracy and adequacy of data in the dental records. Methods An online self‐administered questionnaire evaluated Australian dentists’ knowledge and behaviours rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 10 publications
9
29
1
Order By: Relevance
“…14 However, a study in Australia showed that even though there was some awareness of forensic odontology amongst practising dentists during their undergraduate years, the dental records were still suboptimal and good practice standards were not applied. 15 These findings were similar to those found in two Indian surveys. 2,16 This particular study in Australia 15 did not discuss how much forensic odontology awareness or exposure the dentists received during their undergraduate years.…”
Section: Subjects Which Would Be Suitable For the Incorporation Of Elsupporting
confidence: 89%
“…14 However, a study in Australia showed that even though there was some awareness of forensic odontology amongst practising dentists during their undergraduate years, the dental records were still suboptimal and good practice standards were not applied. 15 These findings were similar to those found in two Indian surveys. 2,16 This particular study in Australia 15 did not discuss how much forensic odontology awareness or exposure the dentists received during their undergraduate years.…”
Section: Subjects Which Would Be Suitable For the Incorporation Of Elsupporting
confidence: 89%
“…Furthermore, a survey of Australian dentists showed that the majority of undergraduate respondents recalled learning about forensic odontology during their education, but there was no exposure to this subject for postgraduates. [19] The reasons for making errors and barriers to accurate and complete record keeping included "lack of time" and "workload" associated with busy dental practices. [19] The need for record keeping guidelines in dental practices (from either the registration authority or a professional association) should be explicitly taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The reasons for making errors and barriers to accurate and complete record keeping included "lack of time" and "workload" associated with busy dental practices. [19] The need for record keeping guidelines in dental practices (from either the registration authority or a professional association) should be explicitly taken into account. [19] In Brazil, law 5081/66 states [20] that dentists working in forensic dentistry can study each subject's neck and head, rather than being limited to the dentition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire development was based on previous similar studies. 10,11,14,[16][17][18][19][20] The researchers comprehensively reviewed the initial draft of questionnaire during several meetings to ensure face and content validity. Once finalised, a pilot testing of the questionnaire was conducted on 20 dentists.…”
Section: Materials and Me Thodsmentioning
confidence: 99%